IMPLEMENTASI KEBIJAKAN PROGRAM KELUARGA HARAPAN DI KECAMATAN NGALIYAN KOTA SEMARANG - Sekar Galih Asmoro; Aufarul Marom; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2021)
Poverty is a major problem felt by the majority of countries, including Indonesia. The government minimizes the problem of poverty by doing the development and implementation of community-based program, the program that PKH. Family Hope Program is a program of social assistance conditional to family and / or poor and vulnerable person enrolled in an integrated data management poverty. This study uses a descriptive qualitative research method. The results of this study indicate that the implementation of the Family Hope Program policy in Ngaliyan District is not in accordance with the objectives of PKH and the supporting and inhibiting factors come from communication, resources, disposition and bureaucratic structure. Suggestions for this research are the need for a communication strategy, take a community approach, increase the number of human resources, and increase the number of allocations and budgets.